First synthesis of (S)-(+)-hymenoic acid, a DNA polymerase λ inhibitor isolated from Hymenochaetaceae sp. Issue 1 (2nd January 2018) - Takahashi, Kensuke; Matsui, Miki; Kuse, Masaki; Takikawa, Hirosato
Abstract: Hymenoic acid, isolated from cultures of the fungus, Hymenochaetaceae sp., is a specific inhibitor of DNA polymerase λ. The first synthesis of ( S )-(+)-hymenoic acid was achieved by starting from trans -1, 4-cyclohexanedimethanol and methyl ( R )-(−)-3-hydroxyisobutyrate, and Julia–Kocienski olefination was employed as the key step. Abstract: : ( S )-(+)-Hymenoic acid, an inhibitor of DNA polymerase λ, was synthesized.